THE RELATIONSHIP BETWEEN MENTAL HEALTH LITERACY AND EMOTIONAL RESILIENCE IN ADOLESCENTS - Azizah Alpia Rahmatika; Herliawati Herliawati; Zulian Effendi; Dhia Diana Fitriani (Jurnal Keperawatan Sriwijaya, 2026)
Aim: Adolescence is a developmental phase characterized by complex physical, psychological, and social changes. Mental health issues among adolescents are a serious concern in Indonesia because they can affect adolescents’ psychological and social well-being as well as their quality of life. This study aims to disclose the relationship between mental health literacy and emotional resilience in students at Public Junior High School 5 (SMP Negeri 5) of Indralaya Utara. Method: This study used a quantitative cross-sectional design. The sample consisted of 166 respondents selected using proportionate stratified random sampling. The data were collected using the Mental Health Literacy Questionnaire-Short Version for Adolescents (MHLq-SVa) to measure mental health literacy and the Growth- Focused Resilience Scale (GFRS) to measure emotional resilience. The data analysis was performed using the Fisher's Exact Test. Result: Majority of the respondents (115) had moderate mental health literacy (69.3%), with 162 respondents having good emotional resilience (97.6%). There was no relationship between mental health literacy and emotional resilience among the students of the Public Junior High School 5 (SMP Negeri 5) of Indralaya Utara with a p-value of 1.000 (>0.05). Conclusion: No relationship between mental health literacy and emotional resilience among the students of the Public Junior High School 5 (SMP Negeri 5) of Indralaya Utara. that students' mental health literacy levels do not always correlate with their emotional resilience.